IMPROVING THE METHODOLOGY OF TEACHING RUSSIAN FOR SPECIFIC PURPOSES IN HIGHER MILITARY EDUCATIONAL INSTITUTIONS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the methodological foundations of teaching Russian for specific purposes in higher military educational institutions. The study highlights the role of CLIL technology, needs analysis, and interactive simulations in the formation of the professional communicative competence of military personnel. The article provides practical recommendations for mastering military terminology and developing skills for working with military-technical documentation in Russian.
Keywords: Military education, Russian language, professional communication, military terminology, CLIL, simulation, Russian as a Foreign Language (RFL), technical documentation.